Optimization of Microwave Reductive Roasting Process of Bauxite Residue - Chiara Cardenia; Efthimios Balomenos; Dimitrios Panias (Metals, 2020)
In this study, microwave-assisted heating is presented as a suitable method to transform the hematite and goethite contained in bauxite residue into magnetite, wüstite, and metallic iron, with a short processing time. The final target was the production of a sinter with strong magnetic properties, allowing the magnetic separation of Fe from the residue. The influence of microwave energy on the sample, the effect of irradiation time, and the carbon/bauxite residue mass ratio (C/BR) were the parameters that have been analyzed to optimize the process. Their optimized combination allowed transforming 79% of the iron present in the sinter into metallic iron. However, hercynite was also formed, and the presence of this mineralogical phase could be considered a possible drawback for its magnetic properties.